Oceanography of the Arabian Sea during the southwest monsoon season Part II: Stratification and circulation (MAUSAM, 1971)
The distribution of mass in the Arabian Sea during the southwest monsoon season, 1963 is presented through several vertical sections and spatial distribution charts of the thermosteric anomaly. The circulation patterns in the upper 200 m are derived. The basic feature of circulation is found to be the formation of several cyclonic and anti-cyclonic cells. Upwelling off the southwest coast of India has been explained on a more rational basis than has been assumed hitherto. It is now attributed partly due to the divergence in the current field and partly due to the cyclonic motion around Laccadive and Maldive Island.